The Effect of Emotional Exhaustion on Employee Turnover Intention at Pangeran Beach Hotel Padang - Azizah; Feri Ferdian (Pt. Threeple Herphi Educate, 2025)
Emotional exhaustion, a central dimension of burnout, is widely recognized as a critical antecedent of employee turnover intention, particularly in high-pressure service sectors such as hospitality. This study investigates the effect of emotional exhaustion on turnover intention among employees of Pangeran Beach Hotel Padang, Indonesia. Adopting a quantitative research design with total sampling, data were collected from 65 employees using a structured questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that emotional exhaustion has a positive and significant impact on turnover intention, indicating that higher levels of emotional depletion substantially increase employees’ propensity to leave the organization. Theoretically, the findings extend burnout and turnover literature by providing empirical evidence from the underexplored Indonesian hospitality context. Practically, this study offers insights for hotel managers to implement targeted interventions—such as workload optimization, emotional support programs, and employee engagement initiatives—to reduce burnout and enhance retention. Limitations include the single-hotel focus and cross-sectional design, suggesting that future research should employ longitudinal and multi-site approaches to improve generalizability.